2019
DOI: 10.1002/app.47851
|View full text |Cite
|
Sign up to set email alerts
|

Oil resistance and low‐temperature characteristics of plasticized nitrile butadiene rubber compounds

Abstract: The mechanical properties and oil resistance of nitrile butadiene rubber as an automotive material are investigated under low‐temperature conditions. We discuss the effects of various plasticizers, such as dioctyl adipate, adipic acid ester, polyether ester, and adipic acid polyester. The mechanical properties after thermal oxidation aging, as well as oil resistance and low‐temperature characteristics of the compounds, are measured using a moving die rheometer, universal testing machine, differential scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
(33 reference statements)
0
10
0
1
Order By: Relevance
“…Therefore, the increase in the disulfide and the monosulfide causes a better the thermal resistance in the rubber [ 38 ]. In addition, the decrease in the mechanical properties of the material through thermal aging was attributed to the formation of new crosslink reactions by residues such as sulfur and the accelerators after application of the thermal aging process [ 41 , 42 , 43 ]. However, thermal aging resistance was observed in the sample and became more prominent after adding more accelerator due to the use of thermally stable monosulfides and disulfides as the accelerators [ 29 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the increase in the disulfide and the monosulfide causes a better the thermal resistance in the rubber [ 38 ]. In addition, the decrease in the mechanical properties of the material through thermal aging was attributed to the formation of new crosslink reactions by residues such as sulfur and the accelerators after application of the thermal aging process [ 41 , 42 , 43 ]. However, thermal aging resistance was observed in the sample and became more prominent after adding more accelerator due to the use of thermally stable monosulfides and disulfides as the accelerators [ 29 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…After 2 min of mixing, the torque values drop to approximately 7.5 N m. This indicates that the choice of adding the PA6 first in the mixer chamber was good, since it favors XNBR processing due to the plasticizer effect of the melting thermoplastic, dispensing the use of plasticizers. [15,16] www.advancedsciencenews.com www.ms-journal.de The addition of POSS in PA/XNBR blends increases the torque needed for processing. Samples 1 and 2 do not show any difference in the final torque.…”
Section: Resultsmentioning
confidence: 99%
“…Physical modification includes adding small molecular plasticizer, adjusting vulcanization formula or rubber sharing. Kim D et al [ 12 ] used various amounts and types of plasticizers to investigate the low temperature resistance of NBR materials. They found that T g of NBR decreased when the plasticizer was added.…”
Section: Introductionmentioning
confidence: 99%